Effects of green manure and doses of NPK on the productivity and architecture of yerba mate (Ilex paraguaiensis) (Research, Society and Development, 2020)
The objective of this work was to evaluate the productivity and architecture of Ilex paraguaiensis under different soil cover and fertilization dosages. The treatments were: Crotalaria juncea L., hog bean (Canavalia ensiformis L.), dwarf pigeon pea (Cajanus cajan L) and Urochloa ruziziensis. Five different doses of NPK mineral fertilizer were used, equivalent to 0 kg, 100 kg, 200 kg, 400 kg and 800 kg ha-1. The design was in randomized blocks with subdivided plots. The evaluations were submitted to analysis of variance and the means to the Tukey test (p